2020
DOI: 10.3390/molecules25061416
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Acanthamoebic Activity of Shoots from in Vitro Cultures and in Vivo Plants of Eryngium alpinum L.—The Endangered and Protected Species

Abstract: Genetically uniform shoots of Eryngium alpinum L. cultured in vitro were subjected to the qualitative analysis applying the UPLC-HESI-HRMS technique. In vitro cultures give the opportunity to perform the phytochemical studies on the protected species without harvesting the plant material from the natural environment. The phytochemical screening of the crude methanolic extracts of shoots, both from in vitro cultures and in vivo plants, revealed the presence of phenolic acids, coumarins, flavonoids, triterpenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…[20]. The phytochemical investigations of E. alpinum revealed the presence of secondary metabolites-triterpenoid saponins [21], phenolic acids mainly caffeic acid, rosmarinic acid and its derivative R-(+)-3'-O-β-d-glucopyranosyl rosmarinic acid, chlorogenic, iso-and neochlorogenic acids, and 3,4-dihydroxyphenylacetic acid [21][22][23], flavonoids-kaempferol, quercetin, and isoquercetin [21,23,24], and the essential oil [25]. The analysis of the essential oil of the E. alpinum aboveground part performed by Dunkić et al [25], showed the presence of oxygenated sesquiterpenes, sesquiterpene hydrocarbons, oxygenated monoterpenes, and monoterpene hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…[20]. The phytochemical investigations of E. alpinum revealed the presence of secondary metabolites-triterpenoid saponins [21], phenolic acids mainly caffeic acid, rosmarinic acid and its derivative R-(+)-3'-O-β-d-glucopyranosyl rosmarinic acid, chlorogenic, iso-and neochlorogenic acids, and 3,4-dihydroxyphenylacetic acid [21][22][23], flavonoids-kaempferol, quercetin, and isoquercetin [21,23,24], and the essential oil [25]. The analysis of the essential oil of the E. alpinum aboveground part performed by Dunkić et al [25], showed the presence of oxygenated sesquiterpenes, sesquiterpene hydrocarbons, oxygenated monoterpenes, and monoterpene hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of L. flos-cuculi, compared to the amoebicidal activity of extracts from other plant species, is fairly high. For example, the effective concentration of an Eryngium alpinum shoot culture extract was 0.5 mg/mL, displaying a similarly high potency of an in vitro-derived material extract rich in triterpenoid saponins [ 39 ]. However, the comparison of IC 50 values for extracts of plants especially effective against Acanthamoeba , including Solidago virgaurea flowers (0.01 mg/mL), Solidago graminifolia flowers (0.05 mg/mL), Pueraria lobata root (0.01 mg/mL), and Rubus chamaemorus leaves (0.05 mg/mL) [ 40 ], shows that only the 80% methanolic fraction of the L. flos-cuculi root extract exerts a similarly strong activity, with IC 50 at 0.06 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids (chlorogenic acid, rosmarinic acid, and its derivative R-(+)-3′ O - β -D-glucopyranosyl rosmarinic acid [ 7 ], as well as caftaric acid, neochlorogenic acid, isochlorogenic acid, 3,4-dihydroxyphenylacetic acid, and caffeic acid [ 8 , 9 ]) have previously been found in this species. Moreover, the group of hydroxycinnamic acid derivates: coumaroylcholine, caffeoylcholine, feruloylquinic acid, dicaffeoylquinic acid, and ferulic acid, and methyl rosmarinate, as well as benzoic acid derivates: glucosyringic acid, trimethoxybenzoic acid, vanillic acid, hydroxyphenyllactic acid, dimethoxybenzaldehyde, glucovanillin, have also been found [ 10 ]. Additionally, flavonoids (quercetin and kaempferol [ 11 ], isoquercetin and quercitrin [ 8 , 9 ], luteolin, luteolin 7- O -glucoside, kaempferol-3- O -rhamnoside, kaempferol-3- O -rutinoside, quercetin-3- O -glucoside, quercetin-3- O -galactoside, quercetin-3- O -rutinoside [ 10 ]) and coumarins (umbelliferone, scopoletin, 4-methylumbelliferyl glucuronide, fraxidin, isofraxidin, scopoline, esculin, dihydroxycoumarin) have been found in this species [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the group of hydroxycinnamic acid derivates: coumaroylcholine, caffeoylcholine, feruloylquinic acid, dicaffeoylquinic acid, and ferulic acid, and methyl rosmarinate, as well as benzoic acid derivates: glucosyringic acid, trimethoxybenzoic acid, vanillic acid, hydroxyphenyllactic acid, dimethoxybenzaldehyde, glucovanillin, have also been found [ 10 ]. Additionally, flavonoids (quercetin and kaempferol [ 11 ], isoquercetin and quercitrin [ 8 , 9 ], luteolin, luteolin 7- O -glucoside, kaempferol-3- O -rhamnoside, kaempferol-3- O -rutinoside, quercetin-3- O -glucoside, quercetin-3- O -galactoside, quercetin-3- O -rutinoside [ 10 ]) and coumarins (umbelliferone, scopoletin, 4-methylumbelliferyl glucuronide, fraxidin, isofraxidin, scopoline, esculin, dihydroxycoumarin) have been found in this species [ 10 ]. The metabolites detected were triterpenoid saponins (3- O – β -D-glucopyranosyl-(1→2)- β -D-glucuronopyranosyl-22- O -angeloyl-R1-barrigenol, 3- O - β -D-glucopyranosyl-(1→2)- β -D-glucuronopyranosyl-22- O -angeloyl-A1-barrigenol) and eryngioside J [ 10 ].…”
Section: Introductionmentioning
confidence: 99%